Computed tomography-based treatment planning for high-dose-rate brachytherapy using the tandem and ring applicator: influence of applicator choice on organ dose and inter-fraction adaptive planning - Dumane, Vishruta A.; Yuan, Yading; Sheu, Ren-Dih; Gupta, Vishal (Journal of Contemporary Brachytherapy, 2017)
Three dimensional planning for high-dose-rate (HDR) brachytherapy in cervical cancer has been highly recommended by consensus guidelines such as the American Brachytherapy Society (ABS) and the Groupe Européen de Curiethérapie – European Society for Radiotherapy and Oncology (GEC-ESTRO). In this document, we describe our experience with computed tomography (CT)-based planning using the tandem/ring applicator. We discuss the influence of applicator geometry on doses to organs at risk (OARs), namely the bladder, rectum, and sigmoid. Through example cases with dose prescribed to point A, we demonstrate how adaptive planning can help achieve constraints to the OARs as per guidelines.